Electrical equivalent modeling of MEMS differential capacitive accelerometer. (May 2020) - Mukhiya, R.; Garg, M.; Gaikwad, P.; Sinha, S.; Singh, A.K.; Gopal, R.
Abstract: The paper presents an electrical equivalent model of Micro-Electro-Mechanical Systems (MEMS) differential capacitive accelerometer. The accelerometer structure is symmetrically suspended using folded beam springs. An electrical equivalent circuit is proposed for the mechanical structure using Force-Current analogy. Electrical circuit model of squeeze air film damping is also taken into account. The simulation results of temperature and pressure variations on the accelerometer for both mechanical and electrical domains are analyzed and compared using MATLAB®, and the results for both the domains are found to be closely matching. The results are compared with the analytical mechanical model of MEMS differential capacitive accelerometer recently reported by Mukhiya et al. (2019) [23]; and are found to be closely matching. The optimum pressure range for operation is found to be 200 ​Pa–300 ​Pa. Settling time is found to be less than 10 ​ms, which also verifies a bandwidth of 100 ​Hz. The proposed model has reasonably good accuracy and requires less computational time in comparison to FEM-based numerical models.